2021
DOI: 10.1186/s12935-021-01983-z
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the UCB HSCs –Derived NK cells Dysfunction through Harnessing RAS/MAPK, IGF-1R and TGF-β Signaling Pathways

Abstract: Background The natural killer (NK) cells differentiated from umbilical cord blood (UCB) hematopoietic stem cells (HSCs) may be more suitable for cell-based immunotherapy compared to the NK cells from adult donors. This is due to the possibility to choose alloreactive donors and potentially more robust in vivo expansion. However, the cytotoxicity of UCB-HSC-derived NK cells against cancer cells might be suboptimal. To overcome this obstacle, we attempted to generate NK cells with potent antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…194 A recent study by Shokouhifar et al highlights the protocol for the generation of natural killer cells from umbilical cord blood hematopoietic stem cells by manipulating RAS/MAPK, IGF-1R and TGF-β signaling pathways that can be used for cancer immunotherapy. 195 RAS associated acquisition of chemoresistance in OC is depicted in Figure 3. Though the mechanism underlying chemoresistance in OC is still ambiguous, numerous such reports suggests the integral role of CSCs in chemoresistance and recurrence.…”
Section: Advancements In Kras Targeted Therapy In Ocmentioning
confidence: 99%
“…194 A recent study by Shokouhifar et al highlights the protocol for the generation of natural killer cells from umbilical cord blood hematopoietic stem cells by manipulating RAS/MAPK, IGF-1R and TGF-β signaling pathways that can be used for cancer immunotherapy. 195 RAS associated acquisition of chemoresistance in OC is depicted in Figure 3. Though the mechanism underlying chemoresistance in OC is still ambiguous, numerous such reports suggests the integral role of CSCs in chemoresistance and recurrence.…”
Section: Advancements In Kras Targeted Therapy In Ocmentioning
confidence: 99%
“…Since in haplo-HSCT conditioning regimen, infections, or residual leukemia cells may induce IL-1 β production, this may influence the NK/ILC3 development from donor-derived CD34+ cells [ 74 ]. Shokouhifar et al found that the differentiation of ex vivo expanded CD34+ cells through manipulation of RAS/MAPK, IGF-1R, and TGF- β signaling pathways is an efficient approach for generating functional NK cells that can be used for cancer immunotherapy [ 83 ]. CD34 + -HSPC cultured in the absence or in the presence of the EZH1/2 inhibitor UNC1999 and EZH2 inhibitor GSK126 showed that UNC1999 and GSK126 increased CD56 + cell proliferation in comparison to the control.…”
Section: The Generation Of Nk Cells and Ilcs From Cd34 + Hscmentioning
confidence: 99%
“…To develop NK cell-based therapies, it is important to find appropriate sources of these cells that minimize cell number limitations, immunological complications, and HLA Donor-Recipient matching [ 89 91 ]. There are several sources of NK cell including peripheral blood (PB), umbilical cord blood (UCB) [ 92 ], bone marrow (BM) and cell lines [ 93 ]. Deriving NK cells from PBMC, hESC and iPSC sources was a revolution which wiped out the worries about the low number and purity of NK cells forever [ 94 ].…”
Section: Nk Cells As the Ancient Warriors Against Cancermentioning
confidence: 99%